Optimization of the Work of Road Transport With the Help of Navigation Equipment on the Example of the Branch of "Mostostroy-11", JSC, TF "Mostootryad-36". (September 2019) - Chikishev, E; Fisher, A; Alontsev, V
Abstract: The article deals with the control of fuel consumption in automotive engineering with the help of navigation equipment. As a result of the experiment on trucks VOLVO FMX 6x4 and Mercedes-Benz Actros 3346S it was found out that the actual fuel consumption is 2-16% lower than the standard. Thus, using the complex of navigation equipment in transport of the company allows not only to significantly reduce fuel costs, but also to optimize control over road flight performance, and also the regime of work and rest of the drivers. As a result of the economic calculation, it was established that the equipment costs are paid off in less than 1 month.